Determinant factor of sharia credit card user in north of Bekasi city - Christophorus Indra Wahyu Putra; Triana Yuniati; Muhammad Richo Rianto; Dody Kurniawan; Agustian Zen (Enrichment : Journal of Management, 2023)
This study is a research that is used to measure the effect of income, financial literacy, credit attitude towards interest in using Sharia credit cards in North of Bekasi City, Indonesia. This research is a quantitative research where the object used is Sharia credit card. The technique used is a probability sampling technique using the Slovin formula. The number of samples used in this study were 100 respondents. The design used in this study is hypothesis testing using the structural equitation model (SEM) – SmartPLS 4.0. The results of this study provide an explanation that the variables of income and financial literacy have no effect on interest in using Sharia credit cards in North of Bekasi City. However, credit attitudes have an influence on interest in using Sharia credit cards in North of Bekasi City This research has a limited object of research which is only carried out on Sharia credit card users in North of Bekasi City. This can be a suggestion for future researchers. The novelty in this study combines the variables of income, financial literacy, credit attitude towards interest in using Sharia credit cards at in North of Bekasi City